PEMIKIRAN PENDIDIKAN FILSUF ISLAM AL-QABISI DAN MUHAMMAD ABDUH - Zainuddin; Zakiyah Thawwifi (Qolamuna : Jurnal Studi Islam, 2023)
Based on the readings related to al-Qabisi's thoughts on Islamic education, it can be concluded that al-Qabisi was a faqih and hafizh of the Qur'an and hadith and someone who understood Arabic well. Thus, the concepts he offers in education tend to be based on the Qur'an and Sunnah, whose paradigms of thought seem normative. However, the environmental conditions at that time still had relevance to the concept he was offering, so that it was used as a guide for teaching children in the fourth century of Hijriyah. Advanced education in al-Qabisi's perspective can be seen from the establishment of a religious environment in various Islamic territories at that time. It is a natural thing if he determines the concept of education which is the guideline in his time. In the view of Muhammad Abduh, Muslims, especially Muslims who are struggling in the world of education, to adhere to Islamic teachings as was done in the (classical) era of the Salaf, meaning that the ijtihad space must be reopened, in order to grow and develop Islamic civilization through education. Keywords: Thought, Philosopher, al-Qobisi, Muhammad Abduh